Detangling Value: A study into the benefits of using in-house CSR expertise compared with the benefits of using CSR consultancy expertise - MacCarthy, Jennifer (2007)
Abstract The topic of Corporate Social Responsibility (CSR) is an area with an increasing breadth of literature. However, literature regarding how CSR expertise is sourced for developing CSR projects and programmes within companies is distinctly weak. This study takes, arguably, the two most predominant forms of CSR expertise, in-house CSR expertise and CSR consultancies, and investigates what value these different types of expertise offer in sourcing for CSR activities. Beyond this, suggestions of when these different forms of expertise are used are discussed. This study also considers if there is a particular formula regarding how CSR expertise is sourced for different projects and programmes. This investigation is based largely on primary research including interviews with CSR representatives from companies that qualified into Business in the Community ÃÂTop 100 Companies that Count in the Corporate Responsibility Index 2006 and interviews with directors of a CSR consultancy. Through this research this study has been able to identify some of the key values of both in-house and CSR consultancy expertise are in the eyes of those who carry out CSR day to day in the business world. It has also been able to shed some light on how these different types of expertise fit together and therefore provide some explanation of how sourcing decisions regarding CSR expertise are made.